Problematika Pendidikan Agama Islam pada Pembentukan Karakter Siswa di Sekolah Dasar Negeri - Amalah, Husnul; Nasirudin, Ahmat; Khusniati, Elvina; Nadhifah, Siti Nurun; Kamila, Muzakiyah (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
This study investigated the problems of Islamic religious education (PAI) learning in forming students' character. This study used a qualitative descriptive method. Data collection techniques in the study included interviews with PAI teachers and students at SDN Somowinangun and observing the learning process in the classroom. The results of this study found three interrelated things. First, the values ​​of character education are included in PAI learning. Second, there are several main problems, namely poor student behavior, such as lack of politeness when talking to teachers and the lack of role of parents in educating children's character, limited class hours, and weak teacher professionalism. Third, schools program methods for habituating commendable behavior in the school environment, providing guidance and religious guidance to students that are adjusted to the values ​​of character education. The results of this study provide an overview of student character issues and the efforts of PAI teachers and schools to overcome these problems.